Igrejas evangélicas e atuação social no Bairro de Felipe Camarão em Natal-RN - Correia, Bruno César Ferreira de Barros (2011)
This work focuses on analysis of the partnerships and socio-religious actions at Felipe Camarão, a popular district situated in the west of the city of Natal-RN. We observed that the inhabitants of this district are facing some economical, political and social difficulties. Coupled to these problems - among them in this study highlight the social violence, committed mainly by young people aged 15 to 29 years, but affects the whole population - we find a location with a large number of evangelical churches. With this, we know the reality of the community more deeply, to thereby be able to understand if there are and how to make partnerships among evangelical churches, the community and other civic organizations in both of the existing district and the city to deal with these problems. In addition, we verified that the elements obstruct the public performance of the churches and also follow the actions already taken